Effect Of Epoxy Materials And Gold Wire Number On Led Encapsulation Process - Zubir, Muhammad Syukri (Universiti Sains Malaysia, 2022)
There are several issues concerning high-power LED application that affect the functionality and reliability of the LED. The most common problems that occurred in LED during the encapsulation process is wire deformation which can affect the life expectancy of the LED. The aim of this present study is to analyse the influence of different epoxy materials and effect of gold wire numbers during the LED encapsulation process. In this study, ANSYS Fluent is utilized to simulate the volume of the epoxy materials being dispense onto the LED by utilizing the volume of fluid (VOF) strategy and user-defined function (UDF). Besides, ANSYS Fluent is also utilized to complete an investigation on the fluid-structure interaction (FSI) phenomena between the gold wire bonding and the epoxy materials. The FSI modelling was used to measure the amount of stresses indirectly applied to the gold wire bonding during the encapsulation process. The simulation is conducted by varying the types of epoxy materials (ERL 4221, EMC and D.E.R.-331) and number of gold wires (1,2,3,4 and 5). An experimental test was conducted to validate the final structure of the epoxy materials obtained from the simulation setup. The results obtained show that the wire deformation, stress and strain distributed on the wire bonding increased with the increasing density of epoxy materials. Besides, the simulation results on the different gold wire numbers showed that the higher the number of gold wires, the larger the stress and strain distributions when the same epoxy material is used.